2007
DOI: 10.1096/fasebj.21.5.a61-d
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen induces the PEMT (phosphatidylethanolamine N‐methyltransferase) gene in human and murine hepatocytes

Abstract: Choline is an essential nutrient for humans, though some part of this requirement can be met by endogenous synthesis catalyzed by phosphatidylethanolamine N‐methyltransferase (PEMT). Human diets which lack sufficient choline intake can result in organ and muscle dysfunction. Pre‐menopausal women are more resistant to choline deficiency than post‐menopausal women and men. There is evidence in animal models which suggests that estrogen can increase PEMT activity. The goal of this study is to investigate whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Lower hepatic PEMT expression was also associated with lower BMI [80], in keeping with the demonstration that PEMT −/− mice are protected from high fat diet-induced obesity and insulin resistance [84,85]. Because the PEMT gene is regulated by estrogen [86,87], the detrimental impact of choline deficiency may be exacerbated following the menopausal transition, consistent with findings from choline depletion [73,88] and observational studies [75]. Together, findings from human and mouse studies suggest that choline deficiency, whether due to low PEMT expression or inadequate dietary intake, may be related to the development of NAFLD and a susceptibility toward progressive disease specifically in lean individuals.…”
Section: Environmental Factorssupporting
confidence: 71%
See 1 more Smart Citation
“…Lower hepatic PEMT expression was also associated with lower BMI [80], in keeping with the demonstration that PEMT −/− mice are protected from high fat diet-induced obesity and insulin resistance [84,85]. Because the PEMT gene is regulated by estrogen [86,87], the detrimental impact of choline deficiency may be exacerbated following the menopausal transition, consistent with findings from choline depletion [73,88] and observational studies [75]. Together, findings from human and mouse studies suggest that choline deficiency, whether due to low PEMT expression or inadequate dietary intake, may be related to the development of NAFLD and a susceptibility toward progressive disease specifically in lean individuals.…”
Section: Environmental Factorssupporting
confidence: 71%
“…For example, postmenopausal women had significantly worse fibrosis compared to premenopausal women, although both groups had similarly low levels of choline intake [75]. As noted above, reduced endogenous production of estrogen results in diminished PEMT expression, which may lead a greater susceptibility to the development of NAFLD in postmenopausal women with chronic states of choline deficiency [86,87].…”
Section: Other Factorsmentioning
confidence: 96%
“…However, the liver employs an additional pathway catalyzed by phosphatidylethanolamine N-methyltransferase (PEMT), which converts PE to PC using three methyl groups from S-adenosylmethionine 45 . Interestingly, PEMT activity exhibits sexual dimorphism 46 and the Pemt gene is regulated by estrogen 47 , 48 . Furthermore, Pemt −/− mice on a high-fat diet display sex-specific differences in their plasma lipoprotein profiles 49 .…”
Section: Discussionmentioning
confidence: 99%
“…An OVX-induced decrease in Pemt was observed in SDT-fatty rats, and a downward trend was also observed in other rat strains. In in vitro, mRNA expression and enzymatic activity of PEMT are upregulated by 17β-estradiol stimulation (Resseguie et al, 2007), and in vivo, NASH models lacking PEMT have been reported to have a worse condition compared to wild-type (Nakatsuka et al, 2016). In SDT-fatty rats, PL synthesis in the liver might be suppressed by the OVX-induced reduction of female hormone levels.…”
Section: Discussionmentioning
confidence: 99%